2018
DOI: 10.1016/j.procbio.2018.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic synthesis of geranyl acetate in packed bed reactor in supercritical carbon dioxide under various pressure-temperature conditions and reactor configurations

Abstract: Data in this paper describes the catalytic performances, expressed in terms of conversion %, of geraniol and acetic acid to geranyl acetate, using the immobilized lipase B from Candida antarctica in packed bed reactors (PBR) using supercritical CO 2 as a solvent. Readers will find data related to different Figures or equations of the article as well as supplementary data that will help to make the difference between flowrates of CO 2 in a liquid state and corresponding flowrates of supercritical CO 2 for vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 13 publications
1
9
1
Order By: Relevance
“…After cycling, cCAL-B@MWCNT, showed a stabilized residual TOF of 4.1 moles of geranyl acetate.mole -1 of CAL-B.min -1 , while twice lower and non-stabilized TOF was achieved with non-covalent binding. When comparing these data with data obtained previously by Bourkaib et al 18 in similar operating conditions but using 300 mg of Lipozyme 435 beads (10.08 % w:w of CAL-B according to dos Santos et al 35 ), it was observed a significantly higher TOF of 62.7 moles of geranyl acetat.mole -1 of CAL-B.min -1 , expected for this commercial meso-macroporous catalyst. Furthermore, development of new biocatalysts using CNTs as support on which CAL-B was covalently or non-covalently immobilized has emerged over the past few years.…”
Section: Geranyl Acetate Synthesis In Scco2supporting
confidence: 75%
See 4 more Smart Citations
“…After cycling, cCAL-B@MWCNT, showed a stabilized residual TOF of 4.1 moles of geranyl acetate.mole -1 of CAL-B.min -1 , while twice lower and non-stabilized TOF was achieved with non-covalent binding. When comparing these data with data obtained previously by Bourkaib et al 18 in similar operating conditions but using 300 mg of Lipozyme 435 beads (10.08 % w:w of CAL-B according to dos Santos et al 35 ), it was observed a significantly higher TOF of 62.7 moles of geranyl acetat.mole -1 of CAL-B.min -1 , expected for this commercial meso-macroporous catalyst. Furthermore, development of new biocatalysts using CNTs as support on which CAL-B was covalently or non-covalently immobilized has emerged over the past few years.…”
Section: Geranyl Acetate Synthesis In Scco2supporting
confidence: 75%
“…In addition, and despite the lower TOF achieved in this study with MWCNTs as carriers versus what was achieved by other authors such as Bourkaib et al with commercial polymeric macroporous beads 18 , it is of great importance to underline the specificity of the present process as compared to the ones observed from literature and also using MWCNTs as carriers. Indeed, when using continuous processing with a packed bed reactor, it was actually not required to perform cycling because reaction products and substrates and CO2 are continuously removed from the reactor at the level of the back-pressure regulator-separator.…”
Section: Geranyl Acetate Synthesis In Scco2contrasting
confidence: 53%
See 3 more Smart Citations